Where has the quest for conception taken us? Lessons from anthropology and sociology - Inhorn, Marcia C. (Reproductive biomedicine & society online, 2020)
Louise Brown, the world’s first test-tube baby, was born more than 40 years ago in England. For Louise Brown’s infertile mother, Lesley, in-vitro fertilization (IVF) was the ‘hope technology’ which allowed her to overcome her tubal infertility after 9 years of heart-breaking involuntary childlessness. Since then, IVF has travelled to diverse global locations, where millions of individuals and couples have embarked on technologically assisted ‘quests for conception’. After 40 years of IVF, where has the quest for conception taken us? This article outlines seven major global trajectories — namely, that the quest for conception has become more: (i) technological, because of a profusion of IVF-based innovations; (ii) masculine, because of men’s eager uptake of intracytoplasmic sperm injection, their own ‘masculine hope technology’; (iii) stratified, due to persistent race- and class-based barriers in IVF access; (iv) transnational, as infertile and other involuntarily childless people search across borders to overcome restrictions in their home countries; (v) selective, as IVF-based reprogenetic technologies eliminate genetic disease while exacerbating sex selection; (vi) moral, as religious sensibilities both accommodate and curtail the possibilities and outcomes of assisted reproductive technology (ART); and (vii) extended, as new cryopreservation technologies prolong the reproductive lifespan and extend reproduction to the transgender community. The article concludes with thoughts on where future quests for conception might take us, and why IVF and other reproductive technologies are ‘good to think with’ in both the anthropology and sociology of reproduction.